Challenges and Strategic Solutions to Guarantee Last Mile Reach for an Indian TB Patient's Nikshay Poshan Yojana; A Conditional Cash Transfer Scheme; Comment on "Does Direct Benefit Transfer Improve Outcomes Among People With Tuberculosis? - A Mixed-Methods Study on the Need for a Review of the Cash Transfer Policy in India" - Harsh Shah (Kerman University of Medical Sciences, 2023)
India has put efforts into the prevention and control of tuberculosis (TB) for more than 50 years. Nikshay Poshan Yojna (NPY) is one of the schemes of conditional cash transfers (CCTs) by the Government of India. The CCT schemes mostly address the demand side constraints. Governments could use this in developing nations as a tool to divert financial resources toward societal development. In India, NPY is more directed toward providing monetary support for a nutritional diet and reducing the catastrophic expenditure of TB patients. Several studies highlighted challenges in implementing cash transfer schemes and provided different operational models. A country like India should address the challenges with defined strategies to ensure its last-mile reach. A present commentary discussing challenges and possible solutions that policy-makers can adapt and set up a support structure to ensure that supportive actions are implemented in response to patient and system side issues.